Faktor – Faktor yang Mempengaruhi Peringkat Obligasi - Aurora Rose Marie; Sufiyati (Masyarakat Ekonomi Syariah Bogor, 2024)
The research was conducted to examine the influence of Company Size, Debt to Equity Ratio, Profitability, and Liquidity on Company Bond Ratings in the Financing Institutions Subsector. The research uses a descriptive method with sample selection in the form of nine companies operating in the non-banking financial industry, especially in the financial institution sub-sector listed on the Indonesia Stock Exchange (BEI) from 2018 to 2022. Data analysis in the research uses descriptive analysis testing, multiple determination coefficient testing, hypothesis testing, and classical assumption testing with the help of statistical tools in the form of SPSS 26.0. Through the research carried out, the results obtained are as follows: 1) Partially, Company Size has a positive and significant influence on the bond rating value 2) Partially, the Debt to Equity Ratio has a negative and significant influence on the bond rating value 3) Partially, Profitability does not have a significant influence on the bond rating value 4) Partially, Liquidity does not have a significant influence on the bond rating value 5) Simultaneously, the Company Size, Debt to Equity Ratio, Profitability, and Liquidity variables have a significant influence on the Bond Rating variable.